358 Trial in progress: A pilot study of combined immune checkpoint inhibition in combination with ablative therapies in subjects with hepatocellular carcinoma (HCC). (10th December 2020) - Carroll, Hailey; Aleem, Umair; Varghese, Pooja; Galligan, Marie; Bourke, Michèle; Hoey, Katherine; Ryan, Ronan; Doran, Peter; Stewart, Stephen; O'Farrelly, Cliona; Greten, Tim; Houlihan, Diarmaid; et al.
Abstract : Background: Locoregional therapies for hepatocellular carcinoma, such as transcatheter arterial chemoembolization (TACE) or ablation, can induce a peripheral anti-tumor immune response. This may be amplified by immune checkpoint inhibitors (ICI). Early and higher anti-CTLA4 dosing could potentially lead to better priming and a stronger immune response. Recent data has suggested that early (Day 1 only), increased doses of anti-CTLA4 therapy, was associated with encouraging clinical activity and a tolerable safety profile. This study will evaluate dual immune checkpoint, CTLA4 (tremelimumab, day 1-only dosing) and PD-L1 (durvalumab) blockade in combination with TACE in patients with advanced HCC. Intensive peripheral immune-monitoring and longitudinal on-treatment tumor biopsies will focus on the role of the innate immune system, particularly Natural Killer cells, in anti-tumor responses. Methods: Patients with HCC (Childs Pugh A/B7; Barcelona Clinic Liver Cancer Stage B/C; ECOG 0/1; sorafenib-naïve or experienced) are being enrolled in a pilot study (Study Number UCDCRC/19/01) of tremelimumab at 2 dose levels (DL1 and DL2) in combination with durvalumab and TACE until disease progression (per irRECIST). DL1: tremelimumab (75 mg q28 days for 4 doses) and durvalumab (1500 mg q28 days). DL2: tremelimumab (300 mg in a single dose on day 1) and durvalumab (1500 mg q28 days). Subtotal TACE will be performed during study week 6 with the dose-limiting toxicity (DLT) evaluation period encompassing the first 8 weeks of the study. Primary endpoint is 6-month progression-free survival with secondary efficacy endpoints being safety, tolerability and overall survival. Exploratory objectives will evaluate changes in immune parameters in the tumor and peripheral blood of patients undergoing anti-CTLA4 therapy pre- and post-RFA or TACE. A major focus will be on the role of the innate immune system, particularly Natural Killer cells, in anti-tumor responses. Patients will be enrolled and treated at St Vincent's University Hospital in Dublin, Ireland. This study is currently open and actively recruiting. Results: N/A Conclusions: N/A Trial Registration: EudraCT Number 2019-002767-98 Ethics Approval: St Vincent's University Hospital Research Ethics Committee Study Number UCDCRC/19/01. References: Duffy AG, Ulahannan SV, Makorova-Rusher O, Rahma O, Wedemeyer H, Pratt D, et al. Tremelimumab in combination with ablation in patients with advanced hepatocellular carcinoma. J Hepatol 2017;66(3):545–51. Lencioni R, Petruzzi P, Crocetti L. Chemoembolization of hepatocellular carcinoma. Semin Intervent Radiol 2013;30(1):3–11. Slovak R, Ludwig JM, Gettinger SN, Herbst RS, Kim HS. Immuno-thermal ablations – boosting the anticancer immune response. Mehta A, Oklu R, Sheth RA. Thermal Ablative Therapies and Immune Checkpoint Modulation: Can Locoregional Approaches Effect a Systemic Response? Gastroenterol Res Pract 2016; 2016 :9251375. Ng J, Dai T. Radiation therapy and the abscopal effect: a concept comes of age. Ann Transl Med 2016;4(6):118. O'Brien MA, Power DG, Clover AJ, Bird B, Soden DM, Forde PF. Local tumour ablative therapies: opportunities for maximising immune engagement and activation. Biochim Biophys Acta 2014; 1846(2):510–23. Kelley RK, Sangro B, Harris WP, Ikeda M, Okusaka T, Kang Y-K, et al. Efficacy, tolerability, and biologic activity of a novel regimen of tremelimumab (T) in combination with durvalumab (D) for patients (pts) with advanced hepatocellular carcinoma (aHCC). Journal of Clinical Oncology 2020;38(15_suppl):4508-. Mariniello A, Novello S, Scagliotti GV, Ramalingam SS. Double immune checkpoint blockade in advanced NSCLC. Crit Rev Oncol Hematol 2020;152 :102980.